Membangun Generasi Cerdas: Pengabdian Mahasiswa KPPM Melalui Kegiatan Mengajar Dan Bimbingan Belajar Di Desa Parparean II - Tiara Sari Surbakti; Parsaoran Silalahi; Helen Valencia Dawolo; Kevin Febrian Sirait; Muhammad Dicky Alamsyah; Aginta Immanuel Purba (CV. Multi Kreasi Media, 2025)
The community service program conducted by Group 3 of KPPM 48 students from Universitas HKBP Nommensen Medan focus on improving educational quality in Parparean II Village through teaching activities and tutoring sessions. This program implemented an interactive learning approach emphasizing discussion and active student participation, involving collaboration between students, SD 173635, and village officials. Activities took place over five days, from February 20, to February 25, 2025, targeting local children. Based on our evaluation, there was 25% increase in participants academic understanding, particularly in Mathematics. Betond academic improvement, the program succesfully fostered learning interest and strengthened social rrelationship between students and the community. This experience not only benefit the children receiving the program but also provided valuable learning for students in understanding educational challenges in rural areas. Active support from the village government and local community was key to the program’s success. It is hoped that this service activity can provide a sustainable impact on improving the quality of human resources in Parparean II Village anda motivating the learning spirit of the local younger generation.